Single molecule magnets sublimated on conducting and magnetic substrates - Malavolti, Luigi (Premio Tesi di Dottorato, 2015)
Single Molecule Magnets (SMMs) showing bistability and quantum phenomena are promising candidates for spintronic applications. In recent years, the study of hybrid surfaces composed of SMMs on conductive and magnetic surfaces has attracted increasing interest. In this work the preparation of hybrid surfaces made by terbium bis(phthalocyaninato) and Fe4 SMMs is reported. The surfaces were structurally and magnetically characterized by means of laboratory and large scale facility techniques. This investigation has provided interesting hints towards their application in spintronic devices and has paved the way for the magnetic characterization of Fe4 at the single molecule level.